Profiles in courage - Kennedy, John F. (John Fitzgerald), 1917-1963.; Kennedy, Caroline, 1957-; Kennedy, Robert F., 1925-1968. (New York : HarperPerennial Modern Classics, 2006)
Describes the courage and conviction demonstrated by eight great patriots at pivotal moments in American history.
Courage and politics -- John Quincy Adams -- Daniel Webster -- Thomas Hart Benton -- Sam Houston -- Edmund G. Ross -- Lucius Quintus Cincinnatus Lamar -- George Norris -- Robert A. Taft -- Other men of political courage -- The meaning of courage.
Special P.S. edition
50th anniversary edition.
Includes bibliographical references (p. 227-237) and index.
Keywords: Legislators -- United States -- Biography; United States. -- Congress. -- Senate -- Biography; Courage -- United States; United States -- Politics and government; United States. -- Congress. -- Senate; Courage; Legislators; Political science; United States; Biography